2021
DOI: 10.1111/trf.16607
|View full text |Cite
|
Sign up to set email alerts
|

Is antivitamin K reversal required in patients with cirrhosis undergoing liver transplantation?

Abstract: Background Antivitamin K agent (AVK) reversal in patients with cirrhosis awaiting liver transplantation (LT) is not defined in guidelines. We investigated the effect of reversion with prothrombin complex concentrate (PCC) on intraoperative transfusion, bleeding, and safety in LT patients on AVK. Study design and methods In 511 patients undergoing LT, we identified 25 patients treated with AVK (AVK group) and 13 patients with incidental portal vein thrombosis (PVT) without AVK (incidental PVT group). Fifty pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the end, five publications were reviewed, four of which were included in the meta-analysis (see Figure 1). One study was excluded from the quantitative analysis because PCC was only administered in a sub-population of LT recipients to reverse anti-vitamin k agents prior to LT [34].…”
Section: Studies Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end, five publications were reviewed, four of which were included in the meta-analysis (see Figure 1). One study was excluded from the quantitative analysis because PCC was only administered in a sub-population of LT recipients to reverse anti-vitamin k agents prior to LT [34].…”
Section: Studies Selectionmentioning
confidence: 99%
“…The mean age was 52.5 (standard deviation, SD: 9.87) years and the mean MELD score was 25.89 (SD: 9.83). Four-factor PCC (Beriplex ® /Kcentra ® , CSL Behring GmbH, Marburg, Germany) was administered in three studies [4,5,34], while two studies [6,7] did not report the type of PCC used. In all studies, viscoelastic tests guided perioperative coagulation management.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[ 59 ] Reversal of LMWH and VKAs have historically been required prior to major surgery; however, a recent study of patients undergoing LT found no difference in bleeding in patients on VKAs who received prothrombin complex concentrate (PCC) compared with those who did not, implying reversal may not be necessary. [ 60 ]…”
Section: Pretransplant Coagulopathy Managementmentioning
confidence: 99%
“…[7,8] This is in line with a larger report that found no difference in intraoperative blood loss or transfusions in patients that were on vitamin K antagonists and given either prothrombin complex concentrate (PCC) or no reversal at the time of liver transplantation. [9] Conversely, Intagliata et al describe switching a patient from apixaban to dabigatran prior to liver transplantation to facilitate reversal prior to surgery with idarucizumab without any blood transfusions given during the operation or new thrombosis. [10] To address this issue, we reviewed management and outcomes of four patients who underwent DDLT who presented for transplant on either apixaban or rivaroxaban.…”
Section: Deceased Donor Liver Transplantation In Patients On Direct O...mentioning
confidence: 99%